2017
DOI: 10.18039/ajesi.292597
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis Of The Support And Training Courses Based On The Views Of The Social Sciences Teachers İn The Context Of The TEOG

Abstract: ÖzTemel Eğitimden Ortaöğretime Geçiş sistemi olarak bilinen TEOG, Türkiye'de 8.sınıf

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The last reason is boredom with constantly being at school or physical reasons such as transportation. Bozbayındır & Kara (2017) and Canpolat & Köcer (2017) also concluded that some parents were not interested in these programs. Instead, they considered private teaching institutions, which they paid, beneficial, and they experienced transportation problems.…”
Section: Discussionmentioning
confidence: 99%
“…The last reason is boredom with constantly being at school or physical reasons such as transportation. Bozbayındır & Kara (2017) and Canpolat & Köcer (2017) also concluded that some parents were not interested in these programs. Instead, they considered private teaching institutions, which they paid, beneficial, and they experienced transportation problems.…”
Section: Discussionmentioning
confidence: 99%
“…(2017a) and Göksu and Gülcü (2016) examined whether the courses fulfill the required goals. Canpolat and Köçer (2017) focused on the opinions of participating teachers to improve the overall effectiveness of the courses.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Hence, not only in Turkey but all around the world, educational institutions are necessary for the success of individuals. Intending to eliminate the expenses for the sake of individuals with low income to be able to get a high level of education, "support and training courses" are opened at schools (Canpolat & Köçer, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations